Aplikasi Penggera Anti-Pencuri - Mohd Nasir, Ahmad Muhaimin Nasha; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2021)
The anti-Theft Alarm app is an android and IoT based app developed with the aim of providing assistance to Nine Speed ​​Adventure Trading bike shop owners. Nowadays, theft cases are very common around the neighborhood. It doesn’t matter whether it’s due to self -negligence or the occurrence of a break -in. Not everyone can afford to have security equipment such as CCTV used as a monitoring tool. This causes those who are unable to have sophisticated safety equipment to bear large or small losses. This often happens in stores whose business is on a small scale or to those who have just started a business. With a look at these vulnerabilities, the anti-Theft Alarm Application was developed as an alternative tool that monitors and alerts users when any theft occurs. Thus, users can prevent the occurrence of any theft. The methodology used to develop this application is the prototype method. The application was developed using Arduino Studio software, Firebase as a database. To develop anti-theft tools using IoT technology, namely Arduino, among the equipment used are NodeMCU ESP8266 WIFI, Arduino UNO, HC-SR04 sensor, breadboard, jumper wire, and even a piezo buzzer. Users can also receive notifications from the sensor via the android app when there is movement detected. It is hoped that this application will be successful to help shop owners to prevent theft activities in his shop located in Kg. Paya Pulai, Temerloh, Pahang. And it is also hoped that this anti-Theft Alarm Application development project will provide positive results and benefits to users and the community.